FOREIGN EXPERIENCE IN MICROFINANCING THE ACTIVITIES OF ENTREPRENEURIAL ENTITIES (E Global Congress, 2025)
According to global experience, microfinancing is a crucial factor in reducing poverty, encouraging entrepreneurship among the population, supporting the development of small business entities, and ensuring the stable growth of the economy. Microfinancing serves as an effective tool for providing financial services to individuals and legal entities who do not have access to traditional banking services due to geographical location, underdeveloped market infrastructure, or high levels of credit risk.